Prevalence of social risks among oncology patients in an integrated health care delivery system. Issue 28 (1st October 2022) - Kumar, Deepika; Zamani, Constanza; Martin, Ernesto; Kolevska, Tatjana; Payne, Jessica; Sheehan, Tammy Rene; Gordon, Nancy P.; Egorova, Olga; Kroenke, Candyce; Neeman, Elad; Liu, Raymond
Abstract : 128 Background: Social risks and needs can affect oncology treatment and outcomes, and some may be amenable to intervention before or during treatment. We surveyed Kaiser Permanente Northern California (KPNC) oncology patients to estimate prevalence of social risks among cancer patients. Methods: Adults undergoing treatment at KPNC infusion centers between 11/2021 – 05/2022 completed a print questionnaire that included questions about recent (past 3 month) financial strains, living, relationship, and transportation situation, and different aspects of social support. Results: A total of 767 patients completed surveys in English. Respondents were 63% female, median age 63y, and majority White (61% White, 19% Asian, 11% Latino, 7% Black) and college-educated (28% some college, 45% ≥ bachelor's degree). About 20% lived alone, 35% were not in a committed relationship, 13% reported they did not usually get the social or emotional support they needed, and 3% often felt lonely or socially isolated. Approximately 24% said they had no one to help them with daily activities (shopping, cooking, transportation, etc.), 8% reported need for more help with daily activities, and 8% indicated that lack of transportation made it hard to get to medical appointments. Patients with no one to help them were more likely to indicate needing more help (14% vs. 6%). Additionally, while undergoing treatment, 6% were also acting as a primary caregiver to someone who was frail, chronically ill, or had a disability. Approximately 18% had experienced at last one recent financial strain, including trouble paying for medical/dental needs (9%), debts (8%), utilities (6%), food (5%), housing (3%), phone/internet (3%), or transportation (2%). Conclusions: Many patients lack adequate emotional and instrumental social support and may also be experiencing difficulties paying for recommended or essential medical and dental needs while undergoing cancer treatment. These findings highlight the importance of incorporating social risk screening into the oncology intake process so that this information is available to the oncology team for care planning and referral to institutional and community resources. In this way, the oncology care team may be able to improve social support and reduce financial and other barriers that may impact patient participation in treatment and treatment outcomes.